It is Not That Bad: Andragogi dalam Psikologi Humanistik untuk Memahami Praktik Pendidikan Tinggi di Indonesia - Haryono, Aloysia Karina (Psychopreneur Journal, 2023)
Abstract. Indonesian higher education has been criticized for falling short of international norms of excellence. Indeed many factors contribute to this phenomenon, and researchers need to understand the underlying mechanism, especially the interaction between the main actors: the lecturers and the students. Therefore, using a qualitative method through observation during class sessions and interviews in one master's program conducted online, this research aims to understand the perspective of both parties, particularly their motivation, and how it is reflected in their behavior. Drawing from Mark Tennent's (2019) interpretation of the andragogy model of adult learning in humanistic psychology, this research found that the dominant student motivation is to follow directions from those who are more powerful instead of pursuing self-actualization. Meanwhile, the lecturer follows the characteristics of the facilitator in the learning process, as stated by Carl Rogers, namely: unconditional positive regard; realness and genuineness; prizing, acceptance, and trust.